The Impact of Fermented Quinoa Sourdough with Enterococcus Strains on the Nutritional, Textural, and Sensorial Features of Gluten-Free Muffins - Souraya Sakoui; Reda Derdak; Fatimazahra Jouga; Amal Dagni; Oana Lelia Pop; Dan Cristian Vodnar; Bernadette-Emőke Teleky; Maria Simona Chis; Carmen Rodica Pop; Laura Stan; Floricuta Ranga; Ramona Suharoschi; et al. (Fermentation)
Gluten-free baked goods exhibit reduced texture and taste characteristics compared to their gluten-containing counterparts. As a result, there is a renewed interest in the fermentation of gluten-free cereals with lactic acid bacteria, which is associated with an improvement in the final baked goods. Quinoa is garnering growing attention due to its different nutrients and bioactive substances, and it is notably employed to build gluten-free goods. In the present study, quinoa flour was fermented with Enterococcus strains (E. gallinarum SL2 and E. mundtii SL1), and further used in the manufacturing of gluten-free muffins. Several analyses were performed on the obtained sourdoughs and muffins, including a viscosity study, a textural and sensory analysis, and a polyphenol, organic acid, and carbohydrate content analysis. The results showed that the fermented quinoa flour exhibited enhanced nutritional value, with increased levels of organic acids such as lactic and acetic acid, as well as improved polyphenol content. The sensory and textural analyses revealed that both Enterococcus strains positively impacted the sensory characteristics and texture of the muffins. Notably, muffins prepared with E. mundtii SL1 demonstrated superior elasticity and overall taste. These results suggest that fermentation with these strains can significantly improve the nutritional profile and sensory quality of gluten-free baked goods, offering a promising approach for the development of healthier and more appealing gluten-free products.